The Neurobiology of X-Linked Intellectual Disability. (October 2013) - Bassani, Silvia; Zapata, Jonathan; Gerosa, Laura; Moretto, Edoardo; Murru, Luca; Passafaro, Maria
X-linked intellectual disability (XLID) affects 1% to 3% of the population. XLID subsumes several heterogeneous conditions, all of which are marked by cognitive impairment and reduced adaptive skills. XLID arises from mutations on the X chromosome; to date, 102 XLID genes have been identified. The proteins encoded by XLID genes are involved in higher brain functions, such as cognition, learning and memory, and their molecular role is the subject of intense investigation. Here, we review recent findings concerning a representative group of XLID proteins: the fragile X mental retardation protein; methyl-CpG-binding protein 2 and cyclin-dependent kinase-like 5 proteins, which are involved in Rett syndrome; the intracellular signaling molecules of the Rho guanosine triphosphatases family; and the class of cell adhesion molecules. We discuss how XLID gene mutations affect the structure and function of synapses.